Efforts to Increase Customer Loyalty Forex Trading Judging from the Elements of Trust and Relationships Emotional - Mhd Ismail Magfur; Nasib Nasib; Debora Tambunan; Ester Hervina Sihombing; Widy Hastuty HS (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2022)
This study aims to determine the effect of trust and emotional relationships partially and simultaneously on customer loyalty in forex trading at the European Rexchanger Trading Company Graha Medan. The research approach used is quantitative research. The population in this study consisted of all customers of the European Rexchanger company Graha Medan Branch, amounting to 2700 people. The sampling technique used was accidental sampling where 96 regular customers at Rexchanger Europe Graha Medan Branch. Questionnaires were selected in this study as a data collection technique. The results of this study partially positive effect on customer trust and emotional relationships partially positive effect on customer trust. Simultaneous test results (Test f) trust and emotional relationships have a positive and significant effect on customer loyalty in Forex trading. The result of the determination test is that 72.7% of the variation in the dependent variable, namely Trust and Emotional Relationships, has a contribution to customer loyalty in Forex trading. While the remaining 28.3% is influenced by other variables outside the variables studied.